Hypotensive effect of endotrabeculectomy as a function of the stage of glaucoma and preoperative intraocular pressure in patients with primary open-angle glaucoma (Ukrainian Journal of Ophthalmology, 2025)
Background: In recent years, minimally invasive glaucoma surgery (MIGS) (particularly, ab interno MIGS) has been actively developed. Various studies have focused on the efficacy of these procedures.Purpose: To assess intraocular pressure (IOP) reduction from baseline after controlled endotrabeculectomy (ETE) in patients with different stages of primary angle glaucoma (POAG) and preoperative IOP levels.Material and Methods: Eighty-eight patients (88 eyes) that received controlled endotrabeculectomy for POAG were included in the study. The 88 patients were divided into two groups based on the stage of glaucoma. In addition, these patients were divided into two other groups based on the preoperative IOP. IOP readings were obtained with a Maklakoff tonometer preoperatively and on day 7 and 1, 3, 6, and 9 and 12 months after surgery. The numbers of hypotensive medications used and visual acuities at the above time points were also noted.Results: The difference between preoperative IOP and postoperative IOP was significant for all groups until month 12 (p < 0.05), irrespective of the stage of glaucoma and the preoperative IOP. The intragroup difference between preoperative and postoperative numbers of hypotensive medications was significant (p < 0.05) for group 1 and group 3 until month 12, for group 2 until month 9, and for group 4 until month 6.  The difference at subsequent time points (month 9 and month 12) was not significant.Conclusion: Controlled endotrabeculectomy can be recommended for patients with stage 1 of stage 2 of glaucoma and/or a baseline IOP of 24 mmHg or lower. In addition, it can be recommended for patients with a baseline IOP of 25 mmHg or higher and patients with stage 3 of stage 4 of glaucoma, but in these cases, one should take into account a high probability of requirement of topical hypotensive medications in the postoperative period.
Keywords: primary open-angle glaucoma; endotrabeculectomy; intraocular pressure; topical hypotensive medication